2022
DOI: 10.2147/dddt.s353494
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Janus Kinase Inhibitors for the Management of Interstitial Lung Disease

Abstract: Interstitial lung disease (ILD) refers to a heterogeneous group of diseases characterized by lung fibroblast proliferation, interstitial inflammation, and fibrosis-induced lung damage. The Janus kinase/signal transducer and activator of transcription (JAK/STAT) pathway is known to be activated by pro-fibrotic/pro-inflammatory cytokines such as IL-6 and IL-13, whose levels are elevated in ILD. The overexpression of growth factors such as transforming growth factor β1 in ILD activates the JAK/STAT pathway throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Previously, we and others demonstrated the pre-fibrotic role of neutrophils/NETs by promoting myofibroblast differentiation and activation in several disease models [ 34 , [53] , [54] , [55] , [56] , [57] ]. In addition, several studies indicated that TF/thrombin and JAK/STAT/cytokines pathways are involved in fibroblast activation and the immunofibrotic process constituting candidate therapeutic targets [ 35 , 39 , [58] , [59] , [60] , [61] , [62] , [63] ]. Recently, results of our group highlighted the importance of inhibiting multiple immune-mediated pathways, to improve survival in severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we and others demonstrated the pre-fibrotic role of neutrophils/NETs by promoting myofibroblast differentiation and activation in several disease models [ 34 , [53] , [54] , [55] , [56] , [57] ]. In addition, several studies indicated that TF/thrombin and JAK/STAT/cytokines pathways are involved in fibroblast activation and the immunofibrotic process constituting candidate therapeutic targets [ 35 , 39 , [58] , [59] , [60] , [61] , [62] , [63] ]. Recently, results of our group highlighted the importance of inhibiting multiple immune-mediated pathways, to improve survival in severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, to COVID-19 lung disease, ILDs are characterized by lung fibroblast activation, interstitial inflammation, and fibrotic lung damage [ 67 ]. Over the last years, multiple mechanism-based immunomodulatory therapies, including tocilizumab or JAK inhibitors, have been used as salvage treatment in refractory and progressive ILDs [ 61 , 68 , 69 ]. Of note, it has been proposed that immunomodulation might be effective particularly in early disease with higher levels of inflammatory activity [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The management and treatment of ILD remains challenging for clinicians. Currently, common therapeutic strategies include glucocorticoids and immunosuppressants (such as cyclophosphamide) ( Shao et al, 2021 ), but sometimes they are resistant to the above-mentioned drugs and have serious adverse reactions ( Huo et al, 2022 ). Therefore, it is urgent to find a drug with significant efficacy and few side effects.…”
Section: Introductionmentioning
confidence: 99%
“…The principal role in ILD patients seems to be played by the JAK2/STAT3 axis. STAT 3 is overexpressed in lung macrophages, endothelial cells, myofibroblasts and neutrophils in idiopathic pulmonary fibrosis (IPF) and systemic sclerosis patients, allowing the deposition of extracellular matrix leading to fibrosis ( 33 ). Finally, transforming growth factor β (TGFβ) is recognized by JAK2-coupled receptors that are highly expressed in fibroblasts, hyperplastic alveolar epithelial type II cells, and in the small pulmonary arteries of IPF patients ( 34 ).…”
Section: Introductionmentioning
confidence: 99%
“…The JAK2/STAT3 pathway therefore mediates TGFβ and IL6 induced pro-fibrotic and pro-inflammatory effects leading to ILD in connective tissue diseases ( 33 ). In a recent in vitro assay, Baricitinib was able to inhibit JAK2/STAT3 and therefore prevent IL6 induced epithelial-mesenchymal transition ( 35 ).…”
Section: Introductionmentioning
confidence: 99%